New therapeutic protocol for improvement of endometrial receptivity (PRIMER) for patients with recurrent implantation failure (RIF) - A pilot study - Dieamant, Felipe; Vagnini, Laura D.; Petersen, Claudia G.; Mauri, Ana L.; Renzi, Adriana; Petersen, Bruna; Mattila, Mariana C.; Nicoletti, Andreia; Oliveira, João Batista A.; Baruffi, Ricardo; Franco Júnior, Jose G. (JBRA assisted reproduction, 2019)
To evaluate whether or not one should use a new Protocol for Endometrial Receptivity Improvement (PRIMER) based on platelet-rich plasma (PRP) and granulocyte colony-stimulation factor (G-CSF) to enhance ongoing pregnancy rates in patients with recurrent implantation failure (RIF). Women undergoing IVF/ICSI were prospectively divided into two groups: - PRIMER/RIF group (n:33): patients with RIF (defined as ≥2embryo transfers (ETs) and at least 5 morphologically good embryos transferred) in which intrauterine PRP injection and subcutaneous G-CSF-injection were performed. - Control group (n:33): patients in their first IVF/ICSI attempt/cycle (without PRP or G-CSF injection). The PRP was prepared using autologous fresh-whole blood processed to increase platelet-concentration in 2 to 4 fold. All patients undergoing the PRP-treatment received 0.7ml of it through intrauterine-injection 48 hours before the ET. G-CSF (300mg/0.5ml) started simultaneously to PRP and was administered subcutaneously every week. Regarding implantation, clinical pregnancy and miscarriage rates, we found no statistically significant difference (18.2% versus 17.6%, p=0.90; 36.4% versus 30.3%, p=0.61 and 25.0% versus 9.0%, p=0.43, respectively). The use of PRIMER enabled RIF patients (previous ET µ: 4.0±1.5) to reach similar ongoing pregnancy and live birth rates like those patients who had their first IVF/ICSI cycle attempt (27.3% versus 27.3%, p=0.99). Our results showed, for the first time, evidence that this therapeutic protocol (PRIMER) could be used as a feasible treatment based on biological rationale for patients with RIF, considering its promising outcomes, it is a simple procedure and not associated with patient complications.